Prevalência e fatores de risco para carreamento de Staphylococcus aureus resistente à meticilina em idosos institucionalizados na cidade de Bauru-SP - Silveira, Mônica da [UNESP] (2013)
The recent increase in the incidence and severity of Staphylococcus aureus gave rise to many studies on its epidemiology in closed institutions. Isolates of methicillin-resistant Staphylococcus aureus (MRSA) are usual agents of infection in hospitals. In recent years, the attention of epidemiologists and clinicians has turned to MRSA of community origin, associated with severe infections of skin and respiratory tract. In this context, nursing homes represent areas of special interest, since they are intermediary institutions between the community and health services. No data on the prevalence of S. aureus and MRSA in nursing homes in Brazil, a country where only 0.8% of the elderly population is institutionalized. This cross-sectional study aimed to identify the prevalence and risk factors for colonization by S. aureus as a whole and MRSA in particular. We enrolled 300 elderly living in nursing homes in the city of Bauru, São Paulo State, Brazil. Colonization was analyzed by collecting nasal swabs of research subjects. Whenever S. aureus was isolated, we performed molecular characterization of methicillin resistance. Additionally, MRSA isolates underwent genotyping by pulsed-field gel electrophoresis (PFGE). For analysis of risk factors, we reviewed the charts of research subjects. Demographics, hospitalizations, procedures and uses of antimicrobials were identified. Univariate and multivariate (logistic regression) were applied. The prevalence identified for S. aureus and MRSA were 17.7% and 3.7%, respectively. Old age and recent hospitalization in hospitals were independent predictors of colonization with S. aureus as a whole, while small or medium-sized facilities and recent hospital admission were associated with carriage of MRSA. In the molecular analysis of 11 MRSA isolates, six were identified as carriers of chromosome cassette SCCmec type II (typically hospital), and two as carriers of SCCmec IV (associated with the community). ...